Shift & night work – the positive impact, challenges and action to deal with it - Abdull Rahman, Rabeatul Husna; Maulad Bahrol, Khadijah; Ismail, Fadillah (Penerbit UTHM, 2020)
Shift work means work that takes place on a schedule of employee outside the normal hours eight at morning until at five at evening. Well, it involves day and night shifts, which is whether in an early morning shifts, and rotating shifts. In Malaysia, shift work happens usually to the health care workers, precision production and repair workers, machines operator, and aviation workers and so on. Especially in manufacturing, employees tend to make sure machines run twenty-four hours per day rather than buying more machines to operate on a day shift.